Safety of the methylene blue plus chloroquine combination in the treatment of uncomplicated falciparum malaria in young children of Burkina Faso [ISRCTN27290841] - Meissner, Peter; Mandi, Germain; Witte, Steffen; Coulibaly, Boubacar; Mansmann, Ulrich; Rengelshausen, Jens; Schiek, Wolfgang; Jahn, Albrecht; Sanon, Mamadou; Tapsoba, Théophile; Walter-Sack, Ingeborg; Mikus, Gerd; et al. (Malaria journal, 2005)
Safe, effective and affordable drug combinations against falciparum malaria are urgently needed for the poor populations in malaria endemic countries. Methylene blue (MB) combined with chloroquine (CQ) has been considered as one promising new regimen.